Factors Associated with Pregnant Women’s Behavior in Preventing Low Birth Weight in the Working Area of Bareng Community Health Center, Malang City - Dea Rahma Diana; Nurul Pujiastuti (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Low Birth Weight (LBW) remains a major neonatal health problem, with a prevalence of 9.2% in the working area of ​​the Bareng Community Health Center in Malang City, the highest compared to other sub-districts. The aim of this study was to identify factors related to pregnant women's behavior in preventing low birth weight (LBW). This study used a quantitative descriptive design with a Cross-Sectional approach. The population in this study was all pregnant women in The working area of ​​the Bareng Community Health Center in Malang City. The sampling technique using total sampling and collected as many as 45 respondents. Data were collected using questionnaires and MCH books, then analyzed bivariately using the chi-square test. The results showed a significant relationship between education factors and the behavior of pregnant women in preventing low birth weight (p-value = 0.018).The higher the education level of pregnant women, the better their behavior in preventing low birth weight (LBW). Efforts to improve LBW prevention behavior can be carried out through ongoing education, increased access to ANC checkups, and family and community involvement in supporting pregnant women.